Financial Risk and Capital Structure: Does it Contribute to Increasing the Company Value of Islamic Banking? - Putra, Satrio Fajar; Oktaviana, Ulfi Kartika (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2022)
This study aimed to determine the effect of financial risk and capital structure on the company value of Islamic commercial banks in 2016-2020. This research uses a quantitative method with a descriptive statistical approach. This research used panel data with analysis tools in panel data regression by Eviews. The sample in this study amounted to 11 Islamic commercial banks with a purposive sampling technique. Purposive sampling aims to obtain samples with specific criteria and follow the research objectives. The results of this study indicate that partially financial risk (NPF) and capital structure (DER) have no effect on company value, and financial risk (FDR) harms company value. Meanwhile, financial risk and capital structure simultaneously affect company value.